METODE ISTINBAT DALAM KITAB TAWDIH AL-AHKAM MIN BULUGH AL-MARAM KARYA AL-BASSAM (1346-1423 H) - Parlindungan Simbolon (JURIS (Jurnal Ilmiah Syariah), 2020)
The tittle of this research: Istinbat Methods in The Book of Tawdih al-Ahkam Min Bulugh al-Maram was Written By al-Bassam (1346-1423 H).  al-Bassam is one of the contemporary Islamic scholar that has succeed in Hadith and Istinbat of the law in his book Tawdih al-Ahkam Min Bulugh al-Maram, before  istinbat, al Bassam had arranged Hadith into its tittle (thematic) and then explained the quality of Hadith and its words. The main problem of this research : how are steps and methods of istinbat al-Bassam? How is istinbat of al-Bassam for ikhtilaf problems?. This research is aimed to find out steps and methods of istinbat al-Bassam in law, istinbat al-Bassam in ikhtilaf problems and istinbat al-Bassam toward contemporary problems. The data of this research was collected through library research that emphasize on textual study. And then the data was analyzed by using content analysis to get the conclusion. This research has found out that al-Bassam before istinbat of law, he had arranged Hadith based on its tittle  and explained quality and its words. Al-Bassam did istinbat of law from the Hadith by using bayani and istislahi method. And then dealing with ikhtilaf al-Bassam was used to methods ‘ard al-aqwal, munaqasyah al-adillah dan al-tarjih.